Pemodelan Knowledge Dalam Proses Pemberian Beasiswa Bagi Mahasiswa Menggunakan Soft System Methodology (SSM) (Studi Kasus : Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura Ambon) - Yulian Hany Makaruku; Eko Sediyono; Irwan Sembiring (Maranatha University Press, 2019)
The process of scholarship awarding especially for the university students through the sub-section of student affairs is influenced by the students’ background and achievements. The background of the students and the process of scholarship awarding in the sub-section of students affairs have the important role to support students’ achievements and academic finance. The method that used in designing knowledge method to this scholarship awarding is the kualitative method with the soft system methodology approach and the steps that added in accordance with the case study. Knowledge management of FKIP Unpatti Ambon is ecpected to work well if there is an interaction between each component and there is no imbalance of the three components, they are knowledge management plot, appropriate technology, and conducive workplace habits. Knowledge management that is modeled using the SSM approach can provide opportunities to FKIP Unpatti Ambon in catching and analysing the information in the faculties. Faculties can implement it strategically in the form of warehousing, and decision support system. The establishment of a process for accessing information to all outside societies through the internet, groupware, and group decision support system is very needed, so that the stakeholders in the fakulties are informed properly, informatively and inovatively. This makes the motivation of knowkedge accumulated from organizational experience.